2008
DOI: 10.1144/sp305.14
|View full text |Cite
|
Sign up to set email alerts
|

Framing volcanic risk communication within disaster risk reduction: finding ways for the social and physical sciences to work together

Abstract: Sixteen years have passed since the last global volcanic event and more than 25 since a volcanic catastrophe that killed tens of thousands. In this time, volcanology has seen major advances in understanding, modelling and predicting volcanic hazards and, recently, an interest in techniques for reducing and mitigating volcanic risk. This paper provides a synthesis of literature relating to this last aspect, specifically the communication of volcanic risk, with a view to highlighting areas of future research int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 61 publications
2
50
0
1
Order By: Relevance
“…Effective collaboration between local and national authorities, as well as trust and frequent communication between local decision-makers, scientists and the population and their representatives are essential elements in the effectiveness of the management of hazardous events (Barclay et al 2008). The awareness by the Mayors and councillors for the need of risk reduction actions, as well as the available means are other key elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective collaboration between local and national authorities, as well as trust and frequent communication between local decision-makers, scientists and the population and their representatives are essential elements in the effectiveness of the management of hazardous events (Barclay et al 2008). The awareness by the Mayors and councillors for the need of risk reduction actions, as well as the available means are other key elements.…”
Section: Discussionmentioning
confidence: 99%
“…Translation of relevant scientific information into understandable language for the local population is yet to be fully implemented in the area, and will facilitate the delivery of more efficient assistance in preparedness and response to natural hazards (e.g. Barclay et al 2008). Previous risk awareness and perception studies have mostly been based on household surveys and found that (volcanic) risk is perceived differently among local scientists (at the University of Buea and the Cameroon Geological Survey) and the local population (Njome et al 2010;Pannaccione Apa et al 2012).…”
Section: Project Motivationmentioning
confidence: 99%
“…Scientific information can be misunderstood, misrepresented or distorted when passed from scientists to end-users (stakeholders, emergency managers and the public; Barclay et al 2008). This can occur when end-users do not comprehend or are unaware of the science being presented, the information is not what is actually needed by end-users, the science is communicated poorly to end-users, or there is a lack of trust between groups (Haynes et al 2007).…”
Section: Communication and Risk Management Strategiesmentioning
confidence: 99%
“…Work in risk communication has demonstrated unequivocally that communication links that are established prior to a crisis are critical in facilitating communication during a crisis (e.g. Marzocchi et al 2012;Barclay et al 2008;Bird et al 2008;Haynes et al 2008). One key recommendation is therefore that experts ensure that they are in communication with civil protection organisations even when volcanic activity is low.…”
Section: The Nature Of Communicationmentioning
confidence: 99%
“…Barclay et al 2008). A frame is a social construct that allows the interpretation of complex information.…”
Section: The Nature Of Communicationmentioning
confidence: 99%